2015
DOI: 10.1002/ase.1509
|View full text |Cite
|
Sign up to set email alerts
|

Development and assessment of a new 3D neuroanatomy teaching tool for MRI training

Abstract: A computerized three-dimensional (3D) neuroanatomy teaching tool was developed for training medical students to identify subcortical structures on a magnetic resonance imaging (MRI) series of the human brain. This program allows the user to transition rapidly between two-dimensional (2D) MRI slices, 3D object composites, and a combined model in which 3D objects are overlaid onto the 2D MRI slices, all while rotating the brain in any direction and advancing through coronal, sagittal, or axial planes. The effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 30 publications
3
66
0
5
Order By: Relevance
“…The use of advancing technology in anatomy education is supported, but it is noted that these tools are to complement how students explore, learn and collaborate in their learning environments and not to replace the existing practices [35]. A previous study examining the effect of a 3D neuroanatomical teaching tool (MRI data sets with 3D neuroanatomical structures overlaid) reported that 79 % of experimental students strongly agreed that it helped to visualize 3D structures and spatial relationships in the brain [6]. The majority (64 %) of students in that study reported they would have preferred user control [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of advancing technology in anatomy education is supported, but it is noted that these tools are to complement how students explore, learn and collaborate in their learning environments and not to replace the existing practices [35]. A previous study examining the effect of a 3D neuroanatomical teaching tool (MRI data sets with 3D neuroanatomical structures overlaid) reported that 79 % of experimental students strongly agreed that it helped to visualize 3D structures and spatial relationships in the brain [6]. The majority (64 %) of students in that study reported they would have preferred user control [6].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study examining the effect of a 3D neuroanatomical teaching tool (MRI data sets with 3D neuroanatomical structures overlaid) reported that 79 % of experimental students strongly agreed that it helped to visualize 3D structures and spatial relationships in the brain [6]. The majority (64 %) of students in that study reported they would have preferred user control [6]. Therefore, self-directed use of anatomy apps may improve students’ learning outcomes on a neuroanatomy assessment.…”
Section: Introductionmentioning
confidence: 99%
“…VR objects simulate an “ideal” US scan allowing the operator to navigate through the 3D US volume in standard orientations, identify the correct plane, and demonstrate the relevant findings. The use of these VR objects displaying normal and abnormal fetal brain findings has been proposed . Nevertheless, there is paucity of evidence demonstrating their actual role in improving the learning process among the trainees.…”
Section: Discussionmentioning
confidence: 99%
“…Since the typically three-dimensional (3D) arrangement of epithelial cells and tissues is closely linked to their functioning, self-explanatory computerised 3D models can make a relevant contribution to students' understanding of the topic, compared to cells and tissues in two-dimensional (2D) representations, such as (virtual) microscopy images (Drapkin, Lindgren, Lopez, & Stabio, 2015). Slide sections, including in virtual microscopy, therefore require students to interpret a range of artefactual changes that occur through cross-sections of a tissue.…”
Section: Introductionmentioning
confidence: 99%